Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to evaluate the derivative of the given function `y = (4x - 1)/(log_2 3)` , hence, you need to differentiate the function with respect to x, such that:

`(dy)/(dx) = (d((4x - 1)/(log_2 3)))/(dx)`

`(dy)/(dx) = 1/(log_2 3)*(d(4x - 1))/(dx)`

`(dy)/(dx) = 1/(log_2 3)*((d(4x))/(dx) - (d(1))/(dx))`

Since differentiating a constant gives 0, yields:

`(dy)/(dx) = 1/(log_2 3)*4`

`(dy)/(dx) = 4/(log_2 3)`

Hence, evaluating the derivative of the given function yields `(dy)/(dx) = 4/(log_2 3).`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question